A preliminary serological study of Trypanosoma evansi and Trypanosoma lewisi in a Chinese human population - Gao, Jiang-Mei; Truc, Philippe; Desquesnes, Marc; Vincendeau, Philippe; Courtois, Patrick; Zhang, Xuan; Li, Su-Jin; Jittapalapong, S.; Lun, Zhao-Rong (Agriculture and Natural Resources, 2018)
Trypanosoma evansi, known as an animal trypanosome, is widely distributed in many countries of Africa, Asia and South America; it causes significant economic loss in these countries. A few cases have also occurred in some countries of Europe due to the importation of infected animals from endemic regions. Rare human T. evansi infections were attended by the health departments and international health organizations in these endemic countries. Trypanosoma lewisi, a cosmopolitan parasite of rats, sometimes found in humans, is currently considered as a zoonotic pathogen and has gained special attention from scientists and international health organizations such as the World Health Organization. The current study considered the serological screening of human infection by T. evansi and T. lewisi in a Chinese human population. None of the 622 samples was found positive for T. evansi infection using the card agglutination test for the trypanosome antigen Rotat 1.2, while, 2.41% of the examined serum samples exhibited some seropositivity to T. lewisi using enzyme-linked immunosorbent assay. No significant difference was found between the samples from areas in the South (Zhaoqing, Guangdong) and Central (Zhengzhou, Henan) China.